Assessment of the response to acetylsalicylic acid in patients with myeloproliferative neoplasms by whole blood assays: A comparison of the PFA-100 with multiple electrode aggregometry. (December 2014) - Robier, Christoph; Neubauer, Manfred; Quehenberger, Franz; Stettin, Mariana; Neumeister, Peter
Abstract Since thrombotic and haemorrhagic complications are the most important causes of morbidity and mortality in myeloproliferative neoplasms (MPN), establishing valid techniques for the monitoring of antiaggregatory treatment would be beneficial. The aim of this study was to assess the aspirin responsiveness in patients with MPN by multiple electrode aggregometry (MEA) and the PFA-100, to determine the concordance rate between the two techniques and to examine a potential clinical impact. Twenty-two consecutive outpatients with polycythaemia vera and essential thrombocythaemia receiving long-time treatment with 100 mg of aspirin were included and clinically re-evaluated within six months after study entry. All subjects were identified as aspirin responders using the PFA-100, whereas only nine (41%) study participants were detected as responders by MEA. The difference in the response rates was statistically highly significant (p < 0.0001). The median aggregation result was 55.5 U (8–123) in the ASPI test, and the median PFA-100 closure time (CT) was 300 sec (221 to 300) in the COL-EPI test. Within the clinical observation period no thrombotic or haemorrhagic events occurred in the study population. In this study we concluded that MEA and the PFA-100 are suitable devices for the detection of a response to aspirin treatment in patients with MPN, but differ significantly in the response rates and thus show a low concordance rate.